Dysfunction of Circulating Natural Killer T Cells in Patients With Scrub Typhus. (30th June 2018) - Kang, Seung-Ji; Jin, Hye-Mi; Cho, Young-Nan; Oh, Tae-Hoon; Kim, Seong Eun; Kim, Uh Jin; Park, Kyung-Hwa; Jang, Hee-Chang; Jung, Sook-In; Kee, Seung-Jung; Park, Yong-Wook
Abstract : Circulating NKT cells are numerically preserved but functionally impaired in patients with scrub typhus. These findings provide important insights into the dynamics of NKT cell responses in mediating and regulating human immune responses against O. tsutsugamushi infection. Abstract: Background: Human natural killer T (NKT) cells are known to serve as regulatory and/or effector cells in infectious diseases. However, little is known about the role of NKT cells in Orientia tsutsugamushi infection. Accordingly, the objective of this study was to examine the level and function of NKT cells in patients with scrub typhus. Methods: This study included 62 scrub typhus patients and 62 healthy controls (HCs). NKT cell level and function in peripheral blood samples were measured by flow cytometry. Results: Proliferation of NKT cells and their ability to produce interferon-γ and interleukin-4 (IL-4) were significantly lower in scrub typhus patients compared to those in HCs. However, circulating NKT cell levels were comparable between patients and HCs. Expression levels of CD69, programmed death-1 (PD-1), lymphocyte activation gene-3 (LAG-3), and T-cell immunoglobulin domain and mucin domain-containing molecule-3 (TIM-3) were significantly increased in scrub typhus patients. Elevated expression of CD69, PD-1, LAG-3, and TIM-3, impaired proliferation, and decreased IL-4 production by NKT cells were recovered in the remission phase. Conclusions: This study demonstrates that circulating NKT cells are numerically preserved but functionally impaired in scrub typhus patients. In addition, NKT cell dysfunction is recovered in the remission phase.